TECHNOLOGIES OF APPLICATION OF MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING (EXAMPLE OF MUSIC LESSONS) - Tilloxo'jaev Orifxon Tursunovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
in connection with the organization of innovative activities on a scientific basis, it is most important to take into account the readiness and interest of students in the implementation of advanced pedagogical technologies in the educational process, as well as to choose the appropriate technology.